Factors affecting student's interest in learning Islamic education - Zaiton, Mustafa; Hishamuddin, Salim (2012)
The main objective of Islamic religious education in Malaysian secondary schools is to inculcate Islamic teachings and values in Muslim students. However, recent studies indicate that students had lesser interest to learn the subject. In response to this phenomenon, this study was carried out to identify the factors that affect students’ interest in learning Islamic education in schools in Malaysia. Data were gathered through in-depth semi-structured interviews with six Form Four students from a selected secondary school in the state of Selangor in central Malaysia. The findings indicate that there are two major factors affecting students’ interest in learning Islamic education which are situational factors and individual factors. The situational factors are: (1) the parents’ influence, (2) the Islamic education teacher’s influence and, (3) the Islamic education curriculum, whereas the individual factors are: (1) initial interest that resides within each individual and, (2) learner diversity in learning. The findings also revealed that the Islamic education teacher is the key factor in affecting students’ interest towards the subject